EXPLORING TEACHERS' PERSPECTIVES ON STUDENT MOTIVATION IN ENGLISH LANGUAGE LEARNING AT MTsN 4 BUTON SELATAN - Syafitri, Nining; Hanafiah, Waode; Adu, Baharudin; Maneba, Sanaria (English Education Journal, 2024)
This research explores teachers' perspectives on strategies to enhance students' motivation in learning English at MTsN 4 Buton Selatan. The research identifies challenges such as student passivity and limited vocabulary, which hinder engagement in language learning. Using a phenomenological approach, data were collected from three teachers through semi-structured interviews and analyzed with NVivo software. The findings highlight that intrinsic motivation, driven by curiosity and personal interest, and extrinsic motivation, influenced by family, peers, and environment, were critical for fostering learning engagement. Teachers employed strategies such as creating supportive classroom environments, assigning meaningful tasks, offering praise, and providing constructive feedback to address motivational barriers. These approaches were crucial in enhancing students' willingness to participate and succeed. This research concludes by emphasizing the importance of holistic and adaptive teaching methods to balance intrinsic and extrinsic motivation for effective learning. Future research could focus on long-term impacts of motivational strategies and sociocultural influences on English language acquisition